Stem Cell-Derived Extracellular Vesicles as Potential Therapeutic Approach for Acute Kidney Injury - Quaglia, Marco; Merlotti, Guido; Colombatto, Andrea; Bruno, Stefania; Stasi, Alessandra; Franzin, Rossana; Castellano, Giuseppe; Grossini, Elena; Fanelli, Vito; Cantaluppi, Vincenzo (Frontiers in Immunology, 2022)
Acute kidney injury is a frequent complication of hospitalized patients and significantly increases morbidity and mortality, worsening costs and length of hospital stay. Despite this impact on healthcare system, treatment still remain only supportive (dialysis). Stem cell-derived extracellular vesicles are a promising option as they recapitulate stem cells properties, overcoming safety issues related to risks or rejection or aberrant differentiation. A growing body of evidence based on pre-clinical studies suggests that extracellular vesicles may be effective to treat acute kidney injury and to limit fibrosis through direct interference with pathogenic mechanisms of vascular and tubular epithelial cell damage. We herein analyze the state-of-the-art knowledge of therapeutic approaches with stem cell-derived extracellular vesicles for different forms of acute kidney injury (toxic, ischemic or septic) dissecting their cytoprotective, regenerative and immunomodulatory properties. We also analyze the potential impact of extracellular vesicles on the mechanisms of transition from acute kidney injury to chronic kidney disease, with a focus on the pivotal role of the complement cascade in this setting. Despite some technical limits, nowadays the development of therapies based on stem cell-derived extracellular vesicles holds promise as a new frontier to limit acute kidney injury onset and progression.